Pengaruh Perceived Value Dan Kepuasan Customer Terhadap Loyalitas Pelanggan Fashion Pada Brand Hadeed.co (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Novi Yulianti Ramadani; Muhammad Agus Salim; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine the influence of Perceived Value and Customer Satisfaction on Fashion Customer Loyalty at the Hadeed.co Brand. This research uses quantitative methods. The population of this study were students of the Faculty of Economics and Business, Islamic University of Malang. The method used is multiple linear regression. In this study, a sample of 55 respondents via Google form was in accordance with the formula used, namely the Malhotra formula. Data analysis in this study used the help of SPSS 26.0 analysis aimed at the Influence of Perceived Value and Customer Satisfaction on Fashion Customer Loyalty at the Hadeed.co Brand. In this study resulted in Perceived Value partially positive and significant effect on Customer Loyalty, and Customer Satisfaction partially positive and significant effect on Customer Loyalty. And for the Influence of Perceived Value (X₁) and Customer Satisfaction (X₂) on Fashion Customer Loyalty (Y) on the Hadeed.co Brand, the study on students of the Faculty of Economics and Business, Islamic University of Malang was 73.8% and the remaining 26.2 was influenced by other variables not present in the study. Keywords : Perceived Value, Customer Satisfaction, and Customer Loyalty.